A dosimetric evaluation of knowledge‐based VMAT planning with simultaneous integrated boosting for rectal cancer patients. (8th November 2016) - Wu, Hao; Jiang, Fan; Yue, Haizhen; Li, Sha; Zhang, Yibao
Abstract : RapidPlan, a commercial knowledge‐based optimizer, has been tested on head and neck, lung, esophageal, breast, liver, and prostate cancer patients. To appraise its performance on VMAT planning with simultaneous integrated boosting (SIB) for rectal cancer, this study configured a DVH (dose‐volume histogram) estimation model consisting 80 best‐effort manual cases of this type. Using the model‐ generated objectives, the MLC (multileaf collimator) sequences of other 70 clinically approved plans were reoptimized, while the remaining parameters, such as field geometry and photon energy, were maintained. Dosimetric outcomes were assessed by comparing homogeneity index (HI), conformal index (CI), hot spots (volumes receiving over 107% of the prescribed dose, V 107 % ), mean dose and dose to the 50% volume of femoral head ( D mean _ FH and D 50 % _ FH ), and urinary bladder ( D mean _ UB and D 50 % _ UB ), and the mean DVH plotting. Paired samples t ‐test or Wilcoxon signed‐rank test suggested that comparable CI were achieved by RapidPlan ( 0.99   ±   0.04 for PTV boost, and 1.03   ±   0.02 for PTV) and original plans ( 1.00   ±   0.05 for PTV boost and 1.03   ±   0.02 for PTV), respectively ( p   >   0.05 ) . Slightly improved HI of planning target volume ( PTV boost ) and PTV were observed in the RapidPlan cases ( 0.05   ±   0.01 for PTV boost, and 0.26   ±   0.01 for PTV) than the original plans ( 0.06   ±   0.01 for PTV boost and 0.26   ±   0.01 for PTV), p   <   0.05 . More cases with positive V 107 % were found in the original (18 plans) than the RapidPlan group (none). RapidPlan significantly reduced the D 50 % _ FH (by 1.53   Gy / 9.86 % from 15.52   ±   2.17 to 13.99   ±   1.16   Gy ), D mean _ FH (by 1.29   Gy / 7.78 % from 16.59 ± 2.07 to 15.30 ± 0.70 G), D 50 % _ UB (by 4.93   Gy / 17.50 % from 28.17 ± 3.07 to 23.24 ± 2.13   Gy ), and D mean _ UB (by 3.94   Gy / 13.43 % from 29.34 ± 2.34 to 25.40 ± 1.36   Gy ), respectively. The more concentrated distribution of RapidPlan data points indicated an enhanced consistency of plan quality. PACS number(s): 87.55.de; 87.55.dk